Toxoplasmosis and Chlamydophilosis in Small Ruminant Farms in Cameroon: Knowledge, Attitudes, Practices, and Perception of Zoonotic Risks of Farmers - Roland Nankam Chimi; Justin Kouamo; Michel Alain Simo Kouam; Muller Dzousse Fotsac; Raphael Chermapi Dembeng; Armelle Prudence Kouengoua Kouengoua; Josué Simo Louokdom; Ferdinand Ngoula (Veterinary Medicine International, 2024)
Zoonotic abortive diseases represent a significant health and economic risk for national public health. This cross-sectional survey was conducted from April to October 2021 among 200 selected small ruminant farmers in the three northern regions of Cameroon. Data collection was done through questionnaires administered by exchange with the herder, and responses were coded and recorded on an Excel spreadsheet. The data were then analyzed with R software, version 2.13.0. An ANOVA test was used to assess significant differences in mean of Knowledge, Attitudes, Practices, and Perception of zoonotic risks (KAPP) scores between regions. Pearson correlations were used to calculate the association between KAPP scores within regions. Small ruminant farmers surveyed had low mean scores for knowledge of abortive toxoplasmosis and chlamydophilosis (0.1 ± 0.2), desirable attitude (0.32 ± 0.07), appropriate practice (0.36 ± 0.13) in managing abortion, and positive perception of zoonotic risks of toxoplasmosis and chlamydophilosis in small ruminants (0.12 ± 0.33), respectively. KAPP was significantly (P<0.01) and positively associated with knowledge (r = 0.98) and risk perception (r = 0.99). However, attitudes (r = 0.06), practices (r = 0.05), and risk perception of toxoplasmosis (r = 0.07) and chlamydophilosis (r = 0.08) were not associated with farmers’ knowledge. This study revealed significant knowledge gaps, low levels of desired attitudes, and high-risk behavioral practices. These results therefore call for capacity building of health professionals and farmers to better integrate the One Health concept in the management of neglected zoonotic diseases.